Illegal drugs, USA policies and Caribbean responses : the road to disaster. - Cumberbatch, Janice A. (1990)
Presents case studies of legislation of Barbados, Jamaica and Montserrat in order that a picture of legal control of drugs in the Region be obtained. Describes Caribbean responses to USA policies to deal with the use of and trafficking in illegal drugs.